Factors predictive of outcome 5 years after matrix-induced autologous chondrocyte implantation in the tibiofemoral joint - Ebert, J.; Smith, Anne; Edwards, P.; Hambly, K.; Wood, D.; Ackland, T. (Sage Publications Inc, 2013)
Background: Matrix-induced autologous chondrocyte implantation (MACI) has become an established technique for the repair of full-thickness chondral defects in the knee. However, little is known about what variables most contribute to postoperative clinical and graft outcomes as well as overall patient satisfaction with the surgery.Purpose: To estimate the improvement in clinical and radiological outcomes and investigate the independent contribution of pertinent preoperative and postoperative patient, chondral defect, injury/surgery history, and rehabilitation factors to clinical and radiological outcomes, as well as patient satisfaction, 5 years after MACI. Study Design: Cohort study; Level of evidence, 3.Methods: This study was undertaken in 104 patients of an eligible 115 patients who were recruited with complete clinical and radiological follow-up at 5 years after MACI to the femoral or tibial condyles. After a review of the literature, a range of preoperative and postoperative variables that had demonstrated an association with postoperative clinical and graft outcomes was selected for investigation. These included age, sex, and body mass index; preoperative 36-item Short Form Health Survey (SF-36) mental component score (MCS) and physical component score (PCS); chondral defect size and location; duration of symptoms and prior surgeries; and postoperative time to full weightbearing gait. The sport and recreation (sport/rec) and knee-related quality of life (QOL) subscales of the Knee Injury and Osteoarthritis Outcome Score (KOOS) were used as the patient-reported clinical evaluation tools at 5 years, while high-resolution magnetic resonance imaging (MRI) was used to evaluate graft assessment. An MRI composite score was calculated based on the magnetic resonance observation of cartilage repair tissue score. A patient satisfaction questionnaire was completed by all patients at 5 years. Regression analysis was used to investigate the contribution of these pertinent variables to 5-year postoperative clinical, radiological, and patient satisfaction outcomes.Results: Preoperative MCS and PCS and duration of symptoms contributed significantly to the KOOS sport/rec score at 5 years, while no variables, apart from the baseline KOOS QOL score, contributed significantly to the KOOS QOL score at 5 years. Preoperative MCS, duration of symptoms, and graft size were statistically significant predictors of the MRI score at 5 years after surgery. An 8-week postoperative return to full weightbearing (vs 12 weeks) was the only variable significantly associated with an improved level of patient satisfaction at 5 years.Conclusion: This study outlined factors such as preoperative SF-36 scores, duration of knee symptoms, graft size, and postoperative course of weightbearing rehabilitation as pertinent variables involved in 5-year clinical and radiological outcomes and overall satisfaction. This information may allow orthopaedic surgeons to better screen their patients as good candidates for MACI, while allowing treating therapists to better individualize their preoperative preparatory and postoperative rehabilitation regimens for a best possible outcome.